PENGARUH PEMBERDAYAAN PSIKOLOGI TERHADAP PERILAKU INOVATIF - Irma Suryani; Halimatussakdiah Halimatussakdiah; Nidia Sofa (Politeknik Negeri Jakarta, 2020)
Linking three dominan factors namely psychological empowerment, innovative work behavior, and intrinsic motivation, this study developed and examined the relationship among them with a mediating factor. Using questionnaire survey from Higher Education Institutions, the study found that pyschological empowerment significantly affect innovative work behavior. In addition, Intrinsic motivation, as anticipated in the study also affect innovative work behavior. Finally, as an intervening variabel, intrinsic motivation enhance the relationship between psychological empowerment and innovative work behavior.